Clinicopathological Characteristics of Plurihormonal Pituitary Adenoma - Shi, Ruoyu; Wan, Xueyan; Yan, Zisheng; Tan, Zhoubin; Liu, Xiaojin; Lei, Ting (Frontiers in Surgery, 2022)
culture supernatant iBackground: As the pathogenesis of plurihormonal pituitary adenoma (PPA) is unclear and the diagnostic criteria are inconsistent, clinicians still find it challenging to diagnose. To analyze the relationship between clinical and pathological characteristics in PPA. Methods: The clinical data of patients with 70 PPAs admitted during 2008–2010 and 2019–2020 were collected and analyzed. In particular, hormone examination using cell culture supernatant was performed to confirm PPA cases from 2019 to 2020. Results: PPA accounted for 13% of all pituitary cases recorded in the same period. There were 30 men and 40 women. Fifty-three percent of patients had one endocrine manifestation, and 1% presented with two endocrine symptoms. However, none of the patients had three endocrine manifestations. The level of one and two types of hormones was elevated in 52 (74.3%) and 5 (7.1%) patients, respectively and that of three types of hormones was increased only in one patient. Immunohistochemical staining for PRL + TSH or FSH/LH was most commonly performed (n = 17), followed by that for PRL + GH + ACTH and PRL + GH + TSH or FSH/LH (n = 14) and PRL + ACTH (n = 10). The primary culture results in vitro were consistent with the pathological findings in five (41.7%) patients. Moreover, 4 of 12 patients diagnosed with PPA during 2019–2020 tested positive for SOX2. Conclusion: The pathogenesis of PPA remains elusive due to the lack of specific clinical symptoms and endocrine changes. Examination of hormones on tumor culture supernatant is helpful for its diagnosis. s helpful for its diagnosis.